Overview on new psychoactive substances in Portugal - Henriques, S.; Silva, J. P.; Hsu, K. (CIES e-Working Paper N.º 217/2018, 2018)
This working paper provides an overview of the phenomenon of new psychoactive substances (NPS) in Portugal, including suggested definitions of NPS, a review of drug policy in Portugal, NPS markets, NPS demand and supply, prevention strategies and insights from expert interviews. NPS emerged in Portugal in 2007, and despite the closure of NPS physical selling points in 2013 and decreasing rates of NPS consumption, the market seems to be continuing with new particularities: a rise in unintentional consumers and the increasing association with problematic drug use. The new trends in users and consumption patterns as well as new forms of communication, acquisition, and production of substances have challenged conventional mechanisms of drug control in Portugal.